Evaluation of moisture sorption and diffusion characteristics of asphalt mastics using manual and automated gravimetric sorption techniques - Apeagyei, Alex K.; Grenfell, James; Airey, Gordon (American Society of Civil Engineers, 2014)
One of the most important factors influencing the durability of asphalt mixtures is moisture-induced damage resulting from the presence and the transport of moisture in pavements. Moisture-induced damage is an extremely complicated phenomenon that is not completely understood but believed to be governed by the interaction of moisture with asphalt mix components (mastic and aggregates). The objective of this study was, therefore, to characterize the sorption and diffusion characteristics of asphalt mastic using gravimetric vapor sorption techniques. Moisture transport, in the hygroscopic region, in asphalt mastics was studied using both static and dynamic gravimetric vapor sorption techniques to determine equilibrium moisture uptake and diffusion coefficients as a function of aggregate and filler types. For the 25-mm diameter thin asphalt mastic films and the testing conditions (23°C and 85% relative humidity) considered, the kinetics of moisture uptake obtained were characteristic of Fickian diffusion with a concentration-dependent diffusion coefficient. Equilibrium moisture uptake and diffusion coefficient estimated from the static measurements were comparable and of the same order of magnitude as those from dynamic sorption techniques. Both measurement techniques ranked the mixes similarly, which suggest either method could be used to characterize moisture transport in asphalt mastics. Equilibrium moisture uptake was relatively higher in mixtures containing granite aggregates compared with limestone aggregate. In contrast, the diffusion coefficient of limestone aggregate mastics was higher than granite. Thus, an inversely proportional relationship exists between moisture uptake and diffusivity of the asphalt mastics studied. The results suggest moisture transport is a function of aggregate type and that both equilibrium moisture uptake and diffusion coefficient are useful in studying moisture susceptibility in asphalt mixtures. The effect of mineral filler type on diffusion coefficient was minimal in the mastics containing granite aggregate but relatively high in mastic samples containing limestone aggregates. Diffusion coefficient was found to increase with sample thickness, which was unexpected because diffusion coefficient (in an isotropic material) is considered an intrinsic property that is independent of sample size. The results suggested anisotropic diffusivity can occur in asphalt mastics and could be attributed to factors, including mineralogy, microstructure, air voids, and the tendency of the aggregates to settle at the bottom of asphalt mastic with time. In addition to characterizing moisture transport in asphalt mastics, the results presented in this paper will be useful as inputs for numerical simulation of moisture damage in asphalt mixtures.